Representación de lo marginal y desigualdad en la expresión artística del rap quiteño. - Herrera Herrera, Paúl Alexander (2018)
The research analyzes the speech of representative Hip Hop culture songs in the city of Quito, in order to identify the probles of marginal and social inequality, this parses two songs from a musical group and an artist, representative of this musical genre, like Mugre Sur and Marmota. Bardin's methodology for the analysis of lyrics was selected, In addition to experts and to the artist themselves, interviews were conducted to understand the cultural manifestation of Hip Hop and its representatives. The analysis considers the social function of the expressions, analyzing: presence, frequency, intensity, direction, order and contingency. In addition to substantiate the research, discussed the context of artist and song. The results show that Hip Hop is a social movement that seeks to open spaces of complaint on the issue of inequality and marginalization, in an population group made invisible, those who through their lyrics express the reality of the streets and therefore put their voice against social, cultural and economic exclusion, against a repressive system, expressing it with intensity, a street, colloquial language, which reflects the reality of the artists, as representatives of these vulnerable groups, with a valid expression that should be studied, as it is part of the reality and urban culture.